The study of comparisons of Muraqabah (self Control) Students Student boarding schools of Jagad 'Alimussirry with the students in the UNESA - Sukma, Muchammad Niki Bagus Wahyune (http://jagadalimussirry.com/, 2019)
The purpose of this research was to analyze the difference in self control students studentboarding schools of Jagad 'alimussirry with the students in the UNESA. This research is both aquantitative approach to the field (field research). Determination of the sample in this research wasconducted with a purposive sampling technique. Based on the engineering samples taken as many as105 subject, 18 students from boarding schools of Jagad ' alimussirry and 87 of the students fromseveral departments. Data collection was done through the dissemination of the scale. The dataanalysis used the t-test is a test that is independent sample test with the help of SPSS (StatisticalProduct and Service Solution) 23.0 version for windows. The results can be seen from the results of atest of the hypothesis gained 0.106 significance so (p > 0.05). This result shows that shows that Ho isaccepted which means no difference a change or an increase in the average value of self control wassignificant between a group of students and students from various PPJA majoring in UNESA.